Reviving the Past and Confronting the Present: Crafts in Syria and Egypt, c. 1875–1925. (2nd January 2020) - Milwright, Marcus
Abstract: The article considers the ways in which traditional manual crafts in Egypt and Syria adapted to the challenges of the importation of mass-produced goods from Europe and changes in taste among local and foreign purchasers. While some crafts did not prosper in this environment, the evidence from surviving objects and primary sources indicates high levels of experimentation, including the creative use of new materials and technologies. The main part of the article presents a case study concerning four undated inlaid brass stands imitating a Mamluk original made for the sultan al-Nasir Muhammad ibn Qalawun in 1327–28. This stand was first exhibited in 1881, and was reproduced in several publications prior to 1900. The study concentrates on the treatment of the inlaid epigraphy, establishing formal differences between the prototype and the copies, as well as pointing out significant divergences between the copies themselves. The latter part of the case study considers the dissemination of specific motifs from the stand of al-Nasir Muhammad onto other types of Mamluk revival metalwork, such as boxes and trays. This comparative analysis offers a means to understand working practices and interrelationships between workshops.